Implementation of Business and Human Rights Principles (UNGPs) in the Protection given to Indonesian Laborers: Gender Perspective - Arsyi Manggali Arya Putra; Nur Putri Hidayah (Jurnal Cita Hukum, 2023)
This research aims to analyze to what extent business and human rights principles have been implemented to protect workers and laborers in Indonesia according to the gender perspective. This research employed a normative method by analyzing the norms set forth in international law synchronized with the provisions in the statute (statutory approach) in Indonesia descriptively and conceptually. The research concludes that Ruggie initiated business and human rights principles as a new concept regarding corporate responsibility to meet the development of human rights. The protection of human rights for workers, especially women, has not been sufficiently given. The management of the dimension of human rights in employment-related matters requires business relations and human rights with the concept of three pillars. First, the state is responsible for preventing violations of human rights. Second, corporations are responsible for respecting human rights. Third, this pillar manages access to the recovery of victims of human rights violations. Furthermore, the protection of workers and laborers is governed by an employment law that needs to be elaborated further by normalizing business and human rights principles in the employment sector.